2020
DOI: 10.1111/1750-3841.15329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chitosan grafted phenolic acid coating on microbiological, physicochemical and protein changes of sea bass (Lateolabrax japonicus) during refrigerated storage

Abstract: This project aimed to evaluate the effects of gallic acid (GA) and protocatechuic acid (PA) grafted onto chitosan (CS) on the improved quality of sea bass (Lateolabrax japonicus) during refrigerated storage. The incorporation of GA and PA onto CS (CS‐g‐GA and CS‐g‐PA) were achieved by the carbodiimide‐mediated grafting procedure. Samples were treated with different solutions (deionized water [CK], 1% CS [m/v], 1% CS‐g‐GA [m/v], and 1% CS‐g‐PA [m/v]) for 10 min, which were then stored at 4 °C. Microbiological q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 52 publications
3
46
0
Order By: Relevance
“…The content of CA in CS-g-phenolic acid products was determined by the Folin-Ciocalteu method. 11 The standard compound was CA (Maclin Biochemical Co. Ltd Shanghai, China). The content of CA was expressed by the phenolic acid standard curve.…”
Section: Methodsmentioning
confidence: 99%
“…The content of CA in CS-g-phenolic acid products was determined by the Folin-Ciocalteu method. 11 The standard compound was CA (Maclin Biochemical Co. Ltd Shanghai, China). The content of CA was expressed by the phenolic acid standard curve.…”
Section: Methodsmentioning
confidence: 99%
“…The TVCs and the counts of psychrophilic bacteria, pseudomonas bacteria, H 2 S-producing bacteria were measured by the plate diffusion method according to the method of Liu et al (2020).…”
Section: Microbiological Analysismentioning
confidence: 99%
“…Moreover, the SAEW-SI sample had the highest hardness value compared to the control and SI sample. After an external force is applied, the ability of samples to return to their original state is called springiness and chewiness is related to the number of chews required to swallow food (Liu et al, 2020). It was observed that neither springiness nor chewiness followed a clear trend in all samples during storage.…”
Section: Tpa Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Sea bass ( Lateolabrax maculatus ) is rich in protein and is the main marine commercial fish in China. Live sea bass are sold at a high price compared to refrigerated and frozen products [ 1 ]. However, the edible value of aquatic products falls sharply during storage.…”
Section: Introductionmentioning
confidence: 99%